Oriental Cockroach, Blatta orientalis Linnaeus (Insecta: Blattaria: Blattidae:) - Kim McCanless (EDIS)
The origin of the oriental cockroach, Blatta orientalis Linnaeus, is uncertain, but it is thought to be from Africa or south Russia. It is a major household pest in parts of the northwest, mid-west, and southern United States. It is also sometimes referred to as the "black beetle" or a "water bug" because of its dark black appearance and tendency to harbor in damp locations. This document is EENY-159, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2000.